`-xe^(-x) + e^(-x) = 0` Solve the equation algebraically. Round your result to three decimal places. Verify your answer using a graphing utility.

Textbook Question

Chapter 3, 3.4 - Problem 75 - Precalculus (3rd Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

kspcr111's profile picture

kspcr111 | In Training Educator

Posted on

-xe^(-x) + e^(-x) = 0

Take the `e^(-x) ` as common ,we get

=>    `e^(-x) [1-x]=0`

=>  ` ((1-x)/(e^x)) =0`

=>   `1-x =0`

=>` x= 1`

Images:
This image has been Flagged as inappropriate Click to unflag
Image (1 of 1)

We’ve answered 318,913 questions. We can answer yours, too.

Ask a question